2019
DOI: 10.2147/opth.s198648
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long-term efficacy and safety of infliximab and cyclosporine combination therapy for refractory uveoretinitis in Beh&ccedil;et&rsquo;s disease</p>

Abstract: This study aimed to evaluate the long-term efficacy and safety of infliximab (IFX) and cyclosporine (CsA) combination therapy for refractory uveoretinitis in Behçet's disease (BD). Patients and methods: The study involved a retrospective review of the medical records of 11 patients with Behçet's uveoretinitis refractory to conventional treatment who had been treated with IFX+CsA combination therapy. The frequency of ocular inflammatory attacks and a Behçet's disease ocular attack score 24 (BOS24) were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
(38 reference statements)
0
6
0
1
Order By: Relevance
“…The characteristics of these studies ( Bawazeer et al., 2010 ; Keino et al., 2011 ; Cantini et al., 2012 ; Okada et al., 2012 ; Al Rashidi et al., 2013 ; Bejerano et al., 2013 ; Calvo-Río et al., 2013 ; Hamuryudan et al., 2013 ; Mesquida et al., 2013 ; Calvo-Río et al., 2014 ; Interlandi et al., 2014 ; Takeuchi et al., 2014 ; Domínguez Casas et al., 2017 ; Fabiani et al., 2017 ; Degirmenci et al., 2018 ; El Garf et al., 2018 ; Martín-Varillas et al., 2018 ; Katsuyama et al., 2019 ; Yalcindag and Kose, 2019 ) were described in Table 1 and Supplementary Table 1 . The 18 articles comprised 968 patients in total and the number of patients in each study ranged from 11 to 164.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of these studies ( Bawazeer et al., 2010 ; Keino et al., 2011 ; Cantini et al., 2012 ; Okada et al., 2012 ; Al Rashidi et al., 2013 ; Bejerano et al., 2013 ; Calvo-Río et al., 2013 ; Hamuryudan et al., 2013 ; Mesquida et al., 2013 ; Calvo-Río et al., 2014 ; Interlandi et al., 2014 ; Takeuchi et al., 2014 ; Domínguez Casas et al., 2017 ; Fabiani et al., 2017 ; Degirmenci et al., 2018 ; El Garf et al., 2018 ; Martín-Varillas et al., 2018 ; Katsuyama et al., 2019 ; Yalcindag and Kose, 2019 ) were described in Table 1 and Supplementary Table 1 . The 18 articles comprised 968 patients in total and the number of patients in each study ranged from 11 to 164.…”
Section: Resultsmentioning
confidence: 99%
“…Pneumonia in 1 patient and depression in 1 patient. Interlandi et al (2014) 12 1.75 0 0 (0) None Katsuyama et al (2019) 11 2 4 0 (0) Urinary tract infection in 1 patient and significant cataract progression in 1 patient. Two patients exhibited transient elevation of serum creatinine levels.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Таким образом, оба препарата эффективны у больных ББ с увеитом, и выбор для конкретного пациента зависит, как правило, от переносимости, предпочтений врача и лекарственного обеспечения. Необходимо отметить, что до настоящего времени практически все исследования эффективности ГИБП в отношении увеита при ББ не относятся к РКИ [25], и в них, за исключением отдельных работ японских [8,26,27] и иранских [28] авторов, не использовались количественные индексы оценки активности увеита.…”
Section: Discussionunclassified
“…Our previous study has shown that infliximab therapy with low-dose cyclosporine is effective in a long-term sustained manner over 4 years of treatment in ocular Behçet's disease [43]. Recently, Katsuyama and colleagues have revealed that infliximab plus cyclosporine combination therapy is welltolerated and can reduce the frequency of ocular attacks over a long period of time without loss of response to infliximab plus cyclosporine combination therapy [44]. On the other hand, Fabiani and colleagues have demonstrated that concomitant immunosuppressive treatment does not affect the infliximab or adalimumab retention rate in ocular Behçet's disease [38,40].…”
Section: Changes Of Frequency Of Ocular Attacks Before and After Initiating Tnf Inhibitormentioning
confidence: 99%